PEMANFAATAN MEDIA SOSIAL TIK TOK SEBAGAI SARANA PENGUATAN IDENTITAS NASIONAL DI ERA PANDEMI - Muhammad Wahyu Nugroho; Supriyono Supriyono; Dadi Mulyadi Nugraha (Academy of Education Journal, 2021)
Social media is one of many solutions in order to communicate with others and get informations in the era of a pandemic. One type of social media that people often used is Tik Tok. This research’s aim is to see the use of social media especially Tik Tok as a medium to strengthen the national identity in the pandemic era. This research uses qualitative descriptive method with the Tik Tok video population as the data. Data was collected using observation, documentation, and recording techniques. From the results of that, an analysis is carried out on each video that can provide reinforcement to Tik Tok application users regarding national identity. The results of this study indicate the strengthening of national identity in Tik Tok social media, such as identity of Indonesian as the national language, the Red and White Flag as the national flag, the Indonesian song Raya as the national anthem, Garuda Pancasila as the national symbol, Bhineka Tunggal Ika as the country's motto, Pancasila as the basis of the state, and regional culture that have been accepted as national culture.